ANALISIS PENYERAPAN TENAGA KERJA PADA USAHA KECIL MENENGAH (UKM) DI KOTA BANJARBARU (STUDI USAHA PERCETAKAN) - Gusti Marliani (Islamic Economics and Business Faculty of UIN Antasari, 2018)
Informal sector become an part of important in replying labor force and employment, one of them development of Small And Medium Industry . Role of small and medium industry in economics of Indonesia have been confessed by wide of society this state moment challenge endless economic crisis. On the other side entrepreneur of printing office have constraint in development of effort him that is problem of capital fee , labour productivity and expenditure of non fee.This research aim to to know fee variable konstribusi, productivity, capital and non fee to absorbtion of labour at effort printing office in Town of Banjarbaru Population in this research is peripatetic Middle Small Industry at Printing office with small scale , with amount of population at the same time sampel counted 36 printing office exist in Town of Banjarbaru.Variable which is used in this research consist of dependent variable which symbol of with ( Y),Labour Employment and free variable. variable independent which symbol with ( X) , that is Effort Printing office with its indicator cover: Fee Labour ( X1), Production Cost ( X2), Work Produktivity (X3), Working Capital ( X4) by using model analyse doubled linear regresi. Result of research indicate that the Effort Printing office ( positive X) Influence and signifikan to Absorbtion Of Labour In Town of Banjarbaru ( Y). Coefficient Determinant ( Adjusted R square) equal to 0,862 meaning that independent variable : variable is Effort Printing office ( X) have contribution equal to 86.2% to variable of dependen : variable Absorbtion of Labour ( Y), while the rest is 13,8% given by other variables which do not the included in this.Informal sector become an part of important in replying labor force and employment, one of them development of Small And Medium Industry . Role of small and medium industry in economics of Indonesia have been confessed by wide of society this state moment challenge endless economic crisis. On the other side entrepreneur of printing office have constraint in development of effort him that is problem of capital fee , labour productivity and expenditure of non fee.This research aim to to know fee variable konstribusi, productivity, capital and non fee to absorbtion of labour at effort printing office in Town of Banjarbaru Population in this research is peripatetic Middle Small Industry at Printing office with small scale , with amount of population at the same time sampel counted 36 printing office exist in Town of Banjarbaru.Variable which is used in this research consist of dependent variable which symbol of with ( Y),Labour Employment and free variable. variable independent which symbol with ( X) , that is Effort Printing office with its indicator cover: Fee Labour ( X1), Production Cost ( X2), Work Produktivity (X3), Working Capital ( X4) by using model analyse doubled linear regresi. Result of research indicate that the Effort Printing office ( positive X) Influence and signifikan to Absorbtion Of Labour In Town of Banjarbaru ( Y). Coefficient Determinant ( Adjusted R square) equal to 0,862 meaning that independent variable : variable is Effort Printing office ( X) have contribution equal to 86.2% to variable of dependen : variable Absorbtion of Labour ( Y), while the rest is 13,8% given by other variables which do not the included in this.